Strengthening Capture Fisheries Information Systems through Data Optimization at Cikidang Fisihing Port, Pangandaran - Khoerunnisa, Nurani; Putra, Pringgo Kusuma Dwi Noor Yadi; Saputra, Yudi Ardiansyah; Hamdani, Galih (Universitas Teuku Umar, 2025)
Sustainable fisheries management requires accurate and digitalized catch data. Cikidang Fishing Port in Pangandaran holds significant potential; however, its current data collection system remains suboptimal. This study aims to formulate a strategy for optimizing fisheries data collection by identifying data flow processes and conducting a SWOT analysis, in order to strengthen an adaptive, accountable, and evidence-based fisheries information system that supports effective governance. The research was conducted at Cikidang Fishing Port involved direct observations and secondary data analysis, followed by the development of an optimization strategy based on internal and external factors derived from the SWOT framework. The result research showed that catch data collection is still predominantly carried out manually, with limited use of the digital Fisheries Port Information Center application. Nonetheless, coordination between data officers and auction stakeholders operates relatively well and serves as a key strength in the data collection process. The strengths of the current system lie in effective communication among staff, the presence of active enumerators, and the availability of basic infrastructure. Identified weaknesses include limited adoption of digital technologies and insufficient human resource capacity. Opportunities include policy support for data digitalization from the Ministry of Marine Affairs and Fisheries and potential cross-sector collaborations. Major threats involve the sustainability of fishery resources and the lack of active participation from fishers in data reporting. The proposed strategies include expanding the implementation of e-logbooks, enhancing enumerator training, strengthening interagency coordination, and conducting educational outreach to fishers. These strategies are expected to foster the development of a more efficient, accurate, and data-driven fisheries data system that supports sustainable fisheries management at the local level.